Entrepreneurial Climate in Establishing and Managing the Business by Women Entrepreneurs of Different Financial Status - Muralikrishna, Panatula; Sangeetha, Neriyanuri (Prabandhan: Indian Journal of Management, 2011)
The success of an organization depends on the interrelationship between management and the work force and the conducive work culture present in the organization. The perception of the employees of the various characteristics of an organization is termed as Organizational Climate. Similarly, the entrepreneurial climate refers to an environment that supports the development of entrepreneurial ventures. Establishing and managing of an enterprise effectively depends on the existing entrepreneurial climate. The present study mainly aims at understanding the entrepreneurial climate (EC) in which the women entrepreneurs establish and manage the enterprises in Andhra Pradesh. This study had been carried out from the point of view of five climatic dimensions namely (1) Reasons for Establishing own Business (REB) ; (2) Experience in Developing an Idea before Establishing the Business (EDIEB) ; (3) Obstacles being faced in Managing the Business (OMB) ; (4) Managerial, Social and Financial Barriers faced in Establishing and Managing the Business (MSFBEMB) and ; (5) Cultural Barriers faced in Managing the Business (CBMB) .The data collected have been analyzed by considering the women entrepreneurs based on investment. The results show that there are no differences in perception and as well in ranking of the entrepreneurial climatic dimensions among low, medium and high investment groups of entrepreneurs, reflecting that the entrepreneurial climate as seen by these different groups is of similar nature.